2009
DOI: 10.1038/jhg.2009.25
|View full text |Cite
|
Sign up to set email alerts
|

The GARS gene is rarely mutated in Japanese patients with Charcot–Marie–Tooth neuropathy

Abstract: Charcot-Marie-Tooth neuropathy (CMT) is an extremely common but heterogeneous inherited neuropathy. It has been classified into two forms: demyelinating and axonal. The dominant axonal form, CMT2, has been further subdivided through linkage study and 15 loci and 10 genes have been reported. For the glycyl-tRNA synthetase (GARS) gene, a CMT2-causing gene, 10 mutations have been reported to date. We studied the GARS in 89 Japanese patients with axonal CMT and detected a novel heterozygous Pro244Leu (c.893C4T) mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…GARS or GDAP1 mutations are very rare and were detected in one patient each. 33 No disease-causing mutation was identified in B80% of patients with axonal CMT. An unknown cause in axonal CMT is more frequent than that in demyelinating CMT.…”
Section: Discussionmentioning
confidence: 99%
“…GARS or GDAP1 mutations are very rare and were detected in one patient each. 33 No disease-causing mutation was identified in B80% of patients with axonal CMT. An unknown cause in axonal CMT is more frequent than that in demyelinating CMT.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 13 CMT-linked mutations on GlyRS (from patients and mice) identified so far (Fig. 1A), two-C201R from ENU-induced mice (corresponding to C157R in the human sequence) and P244L from a Japanese patient-were published recently (10,13). Before carrying out the conformational studies in solution, we determined that the two newly identified CMTassociated residues P244 and C157, like the other 11, were localized near the dimer interface (Fig.…”
Section: Dimer Interface Localization Of Two Newly Identified Cmt-assmentioning
confidence: 99%
“…We describe clinical findings of a Japanese patient with CMT2D with a novel mutation of the GARS. The gene mutation of this patient has been reported in a recent genetic study on CMT neuropathies in Japan [2].A 10-year-old boy with normal birth and development who could not run fast from his early childhood noticed weakness of the fingers. On admission at the age of 15, he showed atrophy in the bilateral thenar, hypothenar, dorsal interossei and tibialis anterior muscles (Fig.…”
mentioning
confidence: 89%